2007
DOI: 10.1016/j.molcatb.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric oxidation of organic sulfides by the filamentous fungi Botrytis cinerea, Eutypa lata and Trichoderma viride

Abstract: The biotransformations of a series of substituted sulfides were carried out with the filamentous fungi Botrytis cinerea, Eutypa lata and Trichoderma viride. Several products underwent microbial oxidation of sulfide to sulfoxide with medium to high enantiomeric purity. With regard to sulfoxide enantioselectivity, the (R)-enantiomer was favoured in biotransformations by T. viride and E. lata while the (S)-enantiomer was favoured in those by B. cinerea. A minor amount of sulfone product was also obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…[36] Moreover, no overoxidation to sulfones was observed, which poses a common drawback among asymmetric sulfoxidations employing chemical [2] or biological catalysts such as Baeyer-Villiger monooxygenases, [13,37] P450 monooxygenases, peroxygenases, and peroxidases. [12,18,38,39] The specific sulfoxidation catalysts described so far mainly give access to (R)enantiomers at lower rates emphasizing the attractiveness of the whole-cell biocatalyst reported here. [40] Interestingly, the BVMO designated 4-hydroxyacetophenone monooxygenase (HAPMO) has been reported to produce highly pure (S)-and (R)enantiomers in dependence of the nature of the sulfide Table 1.…”
Section: Resultsmentioning
confidence: 91%
“…[36] Moreover, no overoxidation to sulfones was observed, which poses a common drawback among asymmetric sulfoxidations employing chemical [2] or biological catalysts such as Baeyer-Villiger monooxygenases, [13,37] P450 monooxygenases, peroxygenases, and peroxidases. [12,18,38,39] The specific sulfoxidation catalysts described so far mainly give access to (R)enantiomers at lower rates emphasizing the attractiveness of the whole-cell biocatalyst reported here. [40] Interestingly, the BVMO designated 4-hydroxyacetophenone monooxygenase (HAPMO) has been reported to produce highly pure (S)-and (R)enantiomers in dependence of the nature of the sulfide Table 1.…”
Section: Resultsmentioning
confidence: 91%
“…Interestingly, the (R)-enantiomer was favored in biotransformations by T. viride and E. lata while the (S)-enantiomer was favored in those by B. cinerea. 189 Chauvin et al reported the asymmetric oxidation of alkyl aryl and dialkyl sulfides using the microalga, Chlorella sorokiniana. These sulfides were converted to sulfoxides in modest yields (up to 67% conversion) and enantioselectivities (up to 58% ee).…”
Section: Scheme 69mentioning
confidence: 99%
“…Whole cell systems for the preparation of chiral sulfoxides are generally more convenient, although the apparent enantioselectivity is sometimes less than that obtained using isolated enzymes. To date, several microorganisms have been used for the asymmetric oxidation of sulfides to sulfoxides, including fungi [14][15][16][17] and bacteria [18][19][20], and to a lesser extent, yeast [21].…”
Section: Introductionmentioning
confidence: 99%